A short film for the prevention of sexual harassment: The final product evaluation - Setiawan, Antonius Ian Bayu; Suwarjo, Suwarjo (ProGCouns: Journal of Professionals in Guidance and Counseling, 2023)
This study aims to determine the effectiveness of the short film "Gerak Bersama" in preventing sexual harassment in high school students. This research is a type of research and development focused on a certain stage, namely focusing on the seventh to the last stage which refers to the Borg & Gall procedure. The subjects in this study were 122 high school students in Sleman Regency. This research produced three short films entitled "Speak Up!", "Enabler?", and "Relasi (Kuasa)" as well as a media guidebook which was examined for the effectiveness of its use in students in cultivating an anti-sexual harassment attitude. The data collection method uses an attitude scale toward sexual harassment. The data analysis technique uses descriptive statistics and an experimental design with T-test and N-Gain analysis. The effectiveness test using the T-test resulted in an average pretest value of 121.72 and a posttest average value of 152.96 and sig. (2-tailed) is 0.000 <0.05 which indicates if there is an average difference between the pretest and posttest. The N-Gain test result is 0.653 which is included in the medium category and the N-Gain value in percentage is 65% which is included in the quite effective category. The short film "Gerak Bersama" was deemed appropriate and effective in preventing sexual harassment of high school students.